Macroids from mixed siliciclastic-carbonate high-frequency sequences of the Agrio Formation (Lower Cretaceous), Neuquén Basin: Palaeoecological and palaeoenvironmental constraints - Caratelli, Martina; Archuby, Fernando M.; Fürsich, Franz; Pignatti, Johannes (Cretaceous Research, 2021)
Macroids, cm-sized biogenically coated grains made of associations of metazoans or protozoans, accumulate in some high-frequency sedimentary sequences of the upper Hauterivian to lower Barremian Agua de la Mula Member of the Agrio Formation in the Neuquén Basin (northern Patagonia, Argentina). The macroids studied are sub-spheroidal and sub-discoidal in shape, 2–3 cm in diameter and 1–2 cm in height. Each macroid is characterised by a rough, weakly bored surface, encrusted by oysters, serpulids, and small, dome-shaped bryozoan colonies. The growth arrangement consists of locally concentric, agglutinated encrusting foraminifers growing above and around skeletal nuclei. The accumulations of macroids on top of some starvation hemi-sequences during the latest Hauterivian 3rd-order transgressive systems tract help in understanding the palaeoenvironmental conditions at the onset of high-frequency regressions, characterised by low but persistent sedimentation rates and a generally low-energy environment. Mineralisation of sand-sized glauconite and apatite grains suggests ephemeral periods of reduced sedimentation or non-deposition. Pyrite framboid size-distribution indicates the upper dysoxic zone with oxygen restrictions. The re-establishment of terrigenous sediment input following transgression promoted eutrophication of the water column. Under such palaeoenvironmental conditions, benthic life was represented mainly by species able to thrive with eutrophicated, oxygen-poor waters at the sediment-water interface. This setting excludes activity of borers during the formation of macroids. Macroids result pivotal in understanding palaeoecology of inherent benthic communities and in refining the interpretation of palaeoenvironmental parameters in mixed siliciclastic-carbonate ramp systems.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Agrio Formation; Benthic foraminifers; Framboidal pyrite; Lower Cretaceous; Sequence stratigraphy